LINK BETWEEN SUSTAINABLE DEVELOPMENT AND EFFECTIVENESS IN REGIONAL GOVERNMENT - JAN ZÁVODNÝ POSPÍŠIL (Challenges of the Knowledge Society)
The paper describes relationship between sustainable development and regional government efficiency. Author defines first sustainable development, its principles and relationship to the public administration area. With usage of systematic review is later defined efficiency in public administration. Based on this information is analyzed relationship between sustainable development and the effectiveness of the management system of regional government.